2012
DOI: 10.4049/jimmunol.1102147
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Deletion Enhances Local Inflammation and Accelerates the Onset of Systemic Inflammatory Response Syndrome

Abstract: The transient receptor potential vanilloid 1 (TRPV1) is primarily localized to sensory nerve fibers and is associated with the stimulation of pain and inflammation. TRPV1 knockout (TRPV1KO) mice show enhanced LPS-induced sepsis compared with wild type (WT). This implies that TRPV1 may have a key modulatory role in increasing the beneficial and reducing the harmful components in sepsis. We investigated immune and inflammatory mechanisms in a cecal ligation and puncture (CLP) model of sepsis over 24 h. CLP TRPV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 53 publications
3
130
0
1
Order By: Relevance
“…These results indicate that TRPV1 protects against LPS-induced organ damage via inhibition of the production of proinflammatory cytokines and chemokines and are consistent with the reports showing that TRPV1 plays a counterregulatory role against acute lung inflammatory injury induced by intratracheal administration of LPS (27). This notion is supported by most recent studies showing that TRPV1 protects against the transition from a local to a systemic inflammatory state in a cecal ligation and puncture (CLP) model of sepsis (28). In addition, it has been shown that the proinflammatory cytokines stimulate expression of adhesion molecules that lead to neutrophil-dependent organ damage (29).…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that TRPV1 protects against LPS-induced organ damage via inhibition of the production of proinflammatory cytokines and chemokines and are consistent with the reports showing that TRPV1 plays a counterregulatory role against acute lung inflammatory injury induced by intratracheal administration of LPS (27). This notion is supported by most recent studies showing that TRPV1 protects against the transition from a local to a systemic inflammatory state in a cecal ligation and puncture (CLP) model of sepsis (28). In addition, it has been shown that the proinflammatory cytokines stimulate expression of adhesion molecules that lead to neutrophil-dependent organ damage (29).…”
Section: Discussionsupporting
confidence: 91%
“…Although the mechanism of TRPV1 channel activation after irradiation is still unknown, possible mediators include radiation-induced reactive oxygen species and secondary generation of nitric oxide in irradiated cells, 33) or radiation-induced extracellular release of ATP from cells, we have reported. [34][35][36][37] On the other hand, it is well known that TRPV1 channel is involved in inflammation and pain sensation, [38][39][40][41] and TRPV1 channel inhibitors are candidates as analgesic drugs to relieve cancer pain. 42,43) Therefore, TRPV1 inhibitors might offer dual benefits in cancer therapy, having both anti-inflammatory and radiosensitizing actions.…”
Section: Resultsmentioning
confidence: 99%
“…5G and 10, C, D, and F) (125,126). In these published studies, the loss of TRPV1 exacerbates the inflammatory response to infection.…”
Section: Discussionmentioning
confidence: 99%